Development Of Automatic Poultry System (Quails) Using Arduino Microcontroller - Azahar, Arman Hadi; Mohd Annuar, Khalil Azha; Harun, Mohamad Haniff; Zainal Abidin, Amar Faiz; Mohd Nor, Rozilawati; Ismail, Muhammad Azizi; Nor Shah, Mohd Badril (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The main purpose of the development of automatic poultry system (quails) using Arduino microcontroller. Quail farmers face problem to maintain or increase their livestock due to high mortality rates during the changes of quail growth phase. The mortality rates mainly affected by uncontrolled climate change of the environment. Therefore, this project is developed to helps broiler quail farmers to maintain their livestock with less supervision from them. At the same time, ensuring stable growth rates and reducing the mortality rates affected from uncontrolled climate/environment factor which is temperature, surround air quality, and intensity of lights is the main focus of this project. In controlling the temperature, air quality, and intensity of light, the DHT11 humidity and temperature sensor, MQ135 air quality sensor, and TSL 2561 digital luminosity (lux) sensor used in this project along with Arduino microcontroller to maintain and control those climate/environment factor at specific range of parameters so that it satisfies with quail growing phases. As the result, it shows that by implement this project can increase performance growth and reduce the mortality rates of the quail compare to conventional method. The retrieved data from the project prototype system and actual experiment is then been analyze, evaluate and kept for further improvements